The influence of posterior medial meniscocapsular lesions on tibiofemoral joint laxity with ACL deficiency and reconstruction. Issue 5 (31st May 2017) - Williams, Andy; Stephen, Jo; Halewood, Camilla; Kittl, Christoph; Amis, Andrew; Bollen, Steve
Introduction: Injury to the posterior medial meniscocapsular junction (the 'ramp' lesion) occurs at the time of anterior cruciate ligament (ACL) rupture (10-24% of cases); however there is a lack of objective evidence investigating how this affects knee kinematics. It is often missed when viewed arthroscopically from the front of the medial compartment as it can only be seen with the arthroscope in the posteromedial recess. Objectives: To investigate the biomechanical impact of the 'ramp lesion' on the ACL deficient and ACL reconstructed knee and the impact of suture repair of the lesion on the same knee states. Methods: Nine fresh frozen cadaveric knees were mounted in a 6 degrees of freedom rig where knee kinematics were recorded at 10° intervals from 0°-100° using an optical tracking system. Measurements were recorded using the following loading conditions: 90 N anterior and posterior tibial forces, 5 Nm internal and external tibial rotation torques, and a combined 90 N anterior tibial force and 5 Nm external tibial rotation torque. Manual Rolimeter readings of anterior translation were taken at 30° and 90°. The knees were tested in the following order: (1) intact, (2) ACL deficient, (3) ACL deficient + posterior meniscocapsule sectioned, (4) ACL deficient + posterior meniscocapsule repaired, (5) ACL patellar tendon reconstruction with posterior meniscocapsule repair and (6) ACL reconstructed + capsular lesion re-created. Statistical analysis was undertaken using repeated-measures ANOVA and post-hoc paired t-tests with Bonferonni correction. Results: Tibial anterior translation and external rotational laxities were both significantly increased compared to the ACL deficient knee following posterior meniscocapsular sectioning ( P < 0.05). These were both restored following ACL reconstruction and meniscocapsular lesion repair ( P > 0.05). Significant changes in anterior tibial translation between the different knee states were identified with the Rolimeter, indicating these changes are clinically detectable ( P < 0.05). Conclusion: Anterior and external rotational laxities were significantly increased after mimicking the 'ramp lesion' by sectioning of the posteromedial meniscocapsular junction in an ACL-deficient knee. These were not restored after ACL reconstruction alone but were restored with ACL reconstruction combined with posterior meniscocapsular repair. Tibial anterior translation changes were clinically detectable by use of the Rolimeter. This study suggests that unrepaired posteromedial meniscocapsular lesions will allow abnormal meniscal and tibiofemoral laxity to persist postoperatively, predisposing the knee to meniscal and articular damage but also adding avoidable extra strain on an ACL graft, which may yield.